THEORETICAL AND PRACTICAL FUNDAMENTALS OF THE ELECTRONIC LITERATURE CREATION SYSTEM - M. Yusupova; Khusanboyeva Tursunoi Muhammadkasimdzhanovna (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, electronic educational literature in the modern education system The theoretical and practical foundations of the electronic educational literature creation system are covered.